The pga gene cluster in Aggregatibacter actinomycetemcomitans is necessary for the development of natural competence in Ca2+‐promoted biofilms. (7th February 2014) - Hisano, K.; Fujise, O.; Miura, M.; Hamachi, T.; Matsuzaki, E.; Nishimura, F.
Summary Natural competence is the ability of bacteria to incorporate extracellular DNA into their genomes. This competence is affected by a number of factors, including Ca2+ utilization and biofilm formation. As bacteria can form thick biofilms in the presence of extracellular Ca2+, the additive effects of Ca2+‐promoted biofilm formation on natural competence should be examined. We evaluated natural competence in Aggregatibacter actinomycetemcomitans, an important periodontal pathogen, in the context of Ca2+‐promoted biofilms, and examined whether the pga gene cluster, required for bacterial cell aggregation, is necessary for competence development. The A. actinomycetemcomitans cells grown in the presence of 1 mm CaCl2 exhibited enhanced cell aggregation and increased levels of cell‐associated Ca2+. Biofilm‐derived cells grown in the presence of Ca2+ exhibited the highest levels of natural transformation frequency and enhanced expression of the competence regulator gene, tfoX. Natural competence was enhanced by the additive effects of Ca2+‐promoted biofilms, in which high levels of pga gene expression were also detected. Mutation of the pga gene cluster disrupted biofilm formation and competence development, suggesting that these genes play a critical role in the ability of A. actinomycetemcomitans to adapt to its natural environment. The Ca2+‐promoted biofilms may enhance the ability of bacteria to acquire extracellular DNA.